Analisis Kepuasan Mahasiswa Terhadap Kualitas Fasilitas Pemondokan di Universitas Sriwijaya - Fadia Fadia; Uswatun Hasanah; Nabila Rosa; Aulia Safitri; Devita Dwi Pertiwi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze student satisfaction with the quality of dormitory facilities at Sriwijaya University. Adequate dormitory facilities are an important factor in supporting student comfort and the smooth running of academic activities. Using a qualitative approach, this research explores students' perceptions of the condition of the facilities and investigates the responses from both dormitory management and the central authority. The results show that students are generally satisfied with aspects such as cleanliness and security but express concerns over the lack of supporting facilities, disruptions in water availability, and the slow response from the management. Based on interviews, dormitory managers stated that the authority for repairs lies with the central office, while the central office acknowledged issues in administrative systems and communication. These findings highlight the need for improved management systems and coordination between parties to enhance the quality of dormitory services.